Esterification of acrylic acid and 2-ethyl hexanol in tubular reactor for the synthesis of 2-ethylhexyl acrylate - Heamamalini, Parathethasan (2017)
Acrylic ester is applied in paper treatment, polishes, leather, fibre, detergents, super-absorbent material plastic additives, textiles, sealant, adhesive and surface coatings (Xu et al., 2006). In recent years, the demand of acrylic esters has been increasing tremendously due to its multiples areas of application. It had a total demand of 3055KT globally in 2013. As the demand increases, the productions of acrylic ester need to be innovated so that it can be produced in a cheaper price. The use of homogeneous catalyst in the commercial process shows that these catalysts are hard to separate from the reaction medium, hence unable the reuse of the catalysts and complicate the separation process. It also promotes side reaction (Kiss, 2011) which resulting in expensive process. In the present study the effect of important operating parameters on the esterification of Acrylic Acid (AA) with 2-Ethyl Hexanol (2EH) for the production of 2-Ethyl Hexyl Acrylate (2EHA) in a tubular reactor was carried out. The reaction is catalysed by a heterogeneous catalyst, PK-208 and the reactants flow at constant flow rate which is 15.7 rpm. The important parameters includes, the range of catalyst weight which are varied from 5 to 15g, the range of molar ratio which are varied from 1:1 to 1:5, whereas the range of the reaction temperature is varied from 75oC to 95oC. Samples with individual volume of 0.5 ml are withdrawn at 1 hour intervals and were analysed using gas chromatography for the composition of 2EHA, AA and 2EH. The results from GC are used to calculate the yield and conversion. The highest yield and conversion was obtained at the temperature of 95oC, initial molar ratio of AA:2EH of 1:3 and catalyst loading of 5 g. The yield is relatively low, this is because the AA may be adsorbed by the resin and increase the loss of AA.